Meningitis and pneumonia in Guatemalan children: the importance of Haemophilus influenzae type b and Streptococcus pneumoniae - Edwin J. Asturias; Monica Soto; Ricardo Menendez; Patricia L. Ramirez; Fabio Recinos; Remei Gordillo; Elizabeth Holt; Neal A. Halsey (Revista Panamericana de Salud Pública, 2003)
OBJECTIVE: To determine the epidemiology of Haemophilus influenzae type b (Hib) and Streptococcus pneumoniae invasive infections in hospitalized Guatemalan children. This is an important issue since Hib vaccine has not been incorporated into the routine immunization program in Guatemala and information from hospital records in 1995 indicated a low incidence of Hib and S. pneumoniae as causes of meningitis and invasive infections. METHODS: Children who were hospitalized in Guatemala City with clinical signs compatible with bacterial infections were evaluated for evidence of Hib or S. pneumoniae infection. Normally sterile body fluids were cultured, and antigen detection was performed on cerebrospinal fluid (CSF) and pleural fluid. RESULTS: Of 1 203 children 1-59 months of age hospitalized over a 28-month period, 725 of them (60.3%) had a primary diagnosis of pneumonia, 357 (29.7%) of meningitis, 60 (5.0%) of cellulitis, and 61 (5.1%) of sepsis and other conditions. Hib was identified in 20.0% of children with meningitis and S. pneumoniae in 12.9%. The average annual incidence of Hib meningitis was 13.8 cases per 100 000 children under 5 years of age, and 32.4% of meningitides caused by Hib and 58.7% of S. pneumoniae meningitides occurred prior to 6 months of age. Case fatality rates were 14.1%, 37.0%, and 18.0%, respectively, for children with Hib, S. pneumoniae, and culture-negative and antigen-negative meningitis. Prior antibiotic therapy was common and was associated with significant reductions in CSF-culture-positive results for children with other evidence of Hib or S. pneumoniae meningitis. CONCLUSIONS: Improvements in case detection, culture methods, and latex agglutination for antigen detection in CSF resulted in identification of Hib and S. pneumoniae as important causes of severe disease in Guatemalan children. Using a cutoff of > 10 white blood cells per cubic millimeter in CSF would improve the sensitivity for detection of bacterial meningitis and help estimate the burden of bacterial meningitis in ...